2000
DOI: 10.1002/1529-0131(200012)43:12<2712::aid-anr11>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of accumulated T cell clonotypes in patients with systemic lupus erythematosus

Abstract: Objective To compare the accumulated T cell clonotypes in peripheral blood (PB) samples obtained at various times, and the accumulated T cell clonotypes in a PB sample and in an affected kidney, from patients with systemic lupus erythematosus (SLE). Methods Peripheral blood mononuclear cells (PBMC) were obtained at 2–4 different times from each of 5 SLE patients, with or without flare‐up of the disease; in addition, a biopsied kidney tissue sample was obtained from 1 of the patients. RNA was extracted from eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
1
21
1
Order By: Relevance
“…In a recent paper by Kato et al [33] oligoclonal expansion of T-cell clonotypes was identified in the PBL of SLE patients. They identified several identical amino acid residues within the CDR3 which are common.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent paper by Kato et al [33] oligoclonal expansion of T-cell clonotypes was identified in the PBL of SLE patients. They identified several identical amino acid residues within the CDR3 which are common.…”
Section: Discussionmentioning
confidence: 96%
“…T cells play an essential role in SLE pathogenesis [15]. Clonal expansion of T cells have been observed in SLE patients’ peripheral blood (PB) [612] and various organs such as skin [13], kidney [8, 1416] and gastrointestinal tract [17] where they may be reactive to local antigens and drive tissue inflammation and injury. In vitro studies show that T cells from SLE patients can recognize and proliferate in response to specific autoantigens such as nucleosomal histones [2, 18] and U1 small nuclear ribonucleoprotein A [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…SLE is a disorder of unknown etiology characterized by marked diversity of organ involvement and fluctuations in disease activity. The disease display a wide range of clinical manifestations such as production of antinuclear autoantibodies, formation of immune complexes, decreased serum complement levels and lymphocytopinea [29]. The initial immunizing agents that cause SLE are unknown but characteristics of immune response in SLE suggest that it is an antigen driven condition.…”
Section: Discussionmentioning
confidence: 99%